2005
DOI: 10.1111/j.1365-2400.2005.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns of largemouth bass in a subtropical US reservoir

Abstract: Nine largemouth bass, Micropterus salmoides Lacepe`de, >1.5 kg were implanted with radio tags and tracked for 1 year in an embayment of Lake Seminole, Georgia, USA. Most largemouth bass movement was <50 m h )1 in all seasons and at all times of day. During the day largemouth bass were offshore in deeper water near large woody structures and moved little. Movement was lower during dusk and night periods, and a general movement towards shoreline areas was evident. Water depths where largemouth bass were located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 21 publications
3
41
0
Order By: Relevance
“…Fish migration between these two pools was unlikely due to locks and dams which hindered upstream and downstream movement (Skinner, 2011;Maceina and Sammons, 2013). In addition, these three fish species are non-migratory and typically exhibit limited movements (Sammons and Maceina, 2005;Radabaugh et al, 2010;Brewer and Orth, 2015). Fish PCB data from three additional pools (Fort Miller,Northumberland,and Waterford;Fig.…”
Section: Study Sitesmentioning
confidence: 96%
“…Fish migration between these two pools was unlikely due to locks and dams which hindered upstream and downstream movement (Skinner, 2011;Maceina and Sammons, 2013). In addition, these three fish species are non-migratory and typically exhibit limited movements (Sammons and Maceina, 2005;Radabaugh et al, 2010;Brewer and Orth, 2015). Fish PCB data from three additional pools (Fort Miller,Northumberland,and Waterford;Fig.…”
Section: Study Sitesmentioning
confidence: 96%
“…1). It is assumed that all small fish were residents of the area in which they were collected, because multiple studies have concluded that largemouth bass have a <5-ha home range, even when habitat is abundant [26]. All largemouth bass in this collection were year 0 to 3 fish (TPWD, unpublished data), 6.5 cm to 30 cm in total length.…”
Section: Fish Collectionsmentioning
confidence: 99%
“…These movements have been studied and described extensively in lakes for both smallmouth bass (see Ridgway et al, 2002) and largemouth bass (Mesing and Wicker, 1986;Sammons and Maceina, 2005). To generalize, adult black basses move into shallow, warm water nesting areas to spawn during spring, typically exhibiting strong spawning site fidelity among years (Ridgway et al, 1991).…”
Section: Introductionmentioning
confidence: 97%
“…After parental care is complete, black basses establish a summer home range that they inhabit until water temperature drops during fall and aggregate in the warmest water possible (sometimes over 20 m deep) during winter (Lewis and Flickinger, 1967;Webster, 1954). Spring nesting areas and overwintering areas are relatively smaller in size than summer home ranges for smallmouth and largemouth bass (Ridgway et al, 2002;Sammons and Maceina, 2005). In general, maximum distance traveled for black basses is positively correlated with the size of the water body (Kaemingk et al, 2011).…”
mentioning
confidence: 96%